(untitled) (Analysis in Theory and Applications, 2018)
In this work, we study existence and uniqueness of solutions for multi-point boundary value problem of nonlinear fractional differential equations with two fractional derivatives. By using the variety of fixed point theorems, such as Banach2019s fixed point theorem, Leray-Schauder2019s nonlinear alternative and Leray-Schauder2019s degree theory, the existence of solutions is obtained. At the end, some illustrative examples are discussed.